Transylvanian Saxon politics and imperial Germany, 1871-1876 - Kwan, Jonathan (Cambridge University Press, 2018)
This article investigates the potential influence of the newly formed Imperial Germany on Transylvanian Saxon politics. The Saxons were German-speaking settlers with long traditions of local autonomy and political privileges within the kingdom of Hungary. From the early eighteenth century, Saxon politics had been defined by its relations to Hungary and to the Habsburg monarchy as a whole. Under the dualist system set up in the 1867 Compromise, the Hungarian government exerted control over Transylvania. The unification of Germany in 1871 introduced a new factor into Saxon politics since there was a clear territorial subject for the indistinct notions of pan-German cultural, religious (Lutheran), and historical affinities. The issue of Saxon administrative and political autonomy, eventually removed by the Hungarian government in 1876, forms a case-study of Saxon politics and the place of Germany within it. There was a spectrum of responses, not simply increased German nationalism amongst Saxons, and the article traces the careers of Georg Daniel Teutsch, Jakob Rannicher, and Guido Baussnern to highlight the diversity within the Saxon camp. From the perspective of Imperial Germany, diplomatic considerations such as regional stability outweighed any possible intervention in Hungarian domestic matters. Moreover, the German public remained largely indifferent to appeals for support.